2012
DOI: 10.1097/tp.0b013e31825c1d41
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Complications After Elective Liver Transplantation—Incidence, Risk Factors, and Outcome

Abstract: Pneumonia is common among patients undergoing LT and is a major cause of morbidity. A restrictive pattern on preoperative pulmonary testing and a higher international normalized ratio measured prior LT were associated with more risk of postoperative pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
114
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 45 publications
(31 reference statements)
5
114
0
1
Order By: Relevance
“…Studies have identified pre-LT risk factors for postoperative pulmonary complications, including age, (3) severity of liver dysfunction, (4)(5)(6) perioperative fluid administration, smoking history, (7) female sex, (4) and preexisting diabetes. (8,9) Few studies have evaluated preexisting pulmonary dysfunction as a risk factor for Abbreviations: CI, confidence interval; COPD, chronic obstructive pulmonary disease; CT, computed tomography; DLCO, diffusing capacity of the lungs for carbon monoxide; ESLD, end-stage liver disease; FEV1, forced expiratory volume in 1 second; FVC, forced vital capacity; ICU, intensive care unit; IQR, interquartile range; LOS, length of stay; LT, liver transplantation; MELD, Model for End-Stage Liver Disease; OR, odds ratio; PFT, pulmonary function test; RV, residual volume; SD, standard deviation; TLC, total lung capacity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have identified pre-LT risk factors for postoperative pulmonary complications, including age, (3) severity of liver dysfunction, (4)(5)(6) perioperative fluid administration, smoking history, (7) female sex, (4) and preexisting diabetes. (8,9) Few studies have evaluated preexisting pulmonary dysfunction as a risk factor for Abbreviations: CI, confidence interval; COPD, chronic obstructive pulmonary disease; CT, computed tomography; DLCO, diffusing capacity of the lungs for carbon monoxide; ESLD, end-stage liver disease; FEV1, forced expiratory volume in 1 second; FVC, forced vital capacity; ICU, intensive care unit; IQR, interquartile range; LOS, length of stay; LT, liver transplantation; MELD, Model for End-Stage Liver Disease; OR, odds ratio; PFT, pulmonary function test; RV, residual volume; SD, standard deviation; TLC, total lung capacity.…”
mentioning
confidence: 99%
“…Postoperative pulmonary complications following liver transplantation (LT) are common and have been associated with increased morbidity and mortality. Infectious complications, prolonged ventilator time, need for reintubation, atelectasis, pleural effusions, acute respiratory distress syndrome, and pulmonary edema have been identified as the main pulmonary complications following LT.(1,2) Both preoperative and intraoperative variables are thought to play a role in the development of pulmonary complications, and although there have been significant advances in critical care and hemodynamic monitoring of LT recipients, pulmonary complications continue to be a significant problem.Studies have identified pre-LT risk factors for postoperative pulmonary complications, including age, (3) severity of liver dysfunction, (4)(5)(6) perioperative fluid administration, smoking history, (7) female sex,and preexisting diabetes. (8,9) Few studies have evaluated preexisting pulmonary dysfunction as a risk factor for Abbreviations: CI, confidence interval; COPD, chronic obstructive pulmonary disease; CT, computed tomography; DLCO, diffusing capacity of the lungs for carbon monoxide; ESLD, end-stage liver disease; FEV1, forced expiratory volume in 1 second; FVC, forced vital capacity; ICU, intensive care unit; IQR, interquartile range; LOS, length of stay; LT, liver transplantation; MELD, Model for End-Stage Liver Disease; OR, odds ratio; PFT, pulmonary function test; RV, residual volume; SD, standard deviation; TLC, total lung capacity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most common isolates are S. aureus, but also enteric gram negative bacteria in abdominal organ recipients. The incidence of pneumonia also varies between organs from 7.3% within the first year after kidney transplant [29] to 22% after liver transplant [30] to 36% in lung transplant recipients [31] and is associated with prolonged intensive care stay and hospital stay. The source of bacterial bloodstream infections after transplant, in addition to intravenous catheters, include the respiratory tract, the urinary tract and the abdomen.…”
Section: Staphylococcus Spp Streptococcus Sppmentioning
confidence: 99%
“…Intensive care unit admission for acute respiratory failure (ARF) after liver transplant is associated with high mortality, morbidity, and increased length of stay in the hospital. [5][6][7] The aim of this study was to evaluate late ICU admission in liver transplant recipients to identify incidences and causes of ARF in the postoperative period and to compare these results with those shown in patients without ARF.…”
Section: Introductionmentioning
confidence: 99%